Reconstitution and functional analysis of kinetochore subcomplexes - Gestaut, Daniel R. (2010)
Kinetochores are multifunctional supercomplexes that link chromosomes to dynamic microtubule tips. Groups of proteins from the kinetochore are arranged into distinct subcomplexes that co-purify under stringent conditions and cause similar phenotypes when mutated. By co-expressing all the components of a given subcomplex from a polycistronic plasmid in bacteria, many labs have had great success in purifying active subcomplexes. This has enabled the study of how the microtubule binding subcomplexes of the kinetochore interact with both the microtubule lattice and dynamic microtubule tips. Here we outline methods for rapid cloning of polycistronic vectors for expression of kinetochore subcomplexes, their purification, and techniques for functional analysis using Total Internal Reflection Fluorescence Microscopy (TIRFM).